Local diagnostic reference levels for paediatric CT brain - Khairulnizan, Nurul Balqis; Mahmud, Mohd Hafizi (Faculty of Medicine, 2026)
High radiation doses from Computed Tomography (CT) scans are the major concern for paediatric patients as they are more susceptible to radiation risk. Hence, diagnostic reference level (DRL) has been implemented to revise CT dose optimization. This study is aimed to determine local DRL of paediatric patients undergoing CT brain examination and compare the proposed DRL with the previously established reports.